2021
DOI: 10.9734/ajaees/2021/v39i130515
|View full text |Cite
|
Sign up to set email alerts
|

Participation, Income Effect and Challenges of Village Savings and Loans Program in Garu and Tempane Districts of the Upper East Region, Ghana

Abstract: Village Savings and Loans Associations (VSLAs), have the aim of reducing poverty and creating assets to rural dwellers who have limited access to formal finance due to high collateral requirements. However, since the implementation of VSLAs in the Garu and Tempane districts for over a decade, there is inadequate evidence as to the impact of VSLAs on the lives of the participants. Not only that, there is the need to find out the current and anticipated challenges faced by the participants in the program. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Consequently, many previous studies (Aaron et al, 2019;Karlan et al, 2017;Lambongang et al, 2020;Mbiro and Ndlovu, 2021;Mwansikilwa et al, 2017;Sienso et al, 2021) have addressed the impact of village saving groups on food and nutrition security and some other welfare indicators. Bannor et al (2020) examined the influence of VSLA on off-farm income and poverty in Ghana and found that VSLA had a significant effect on off-farm income.…”
Section: Overview and Concept Of Vsla In Ghanamentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, many previous studies (Aaron et al, 2019;Karlan et al, 2017;Lambongang et al, 2020;Mbiro and Ndlovu, 2021;Mwansikilwa et al, 2017;Sienso et al, 2021) have addressed the impact of village saving groups on food and nutrition security and some other welfare indicators. Bannor et al (2020) examined the influence of VSLA on off-farm income and poverty in Ghana and found that VSLA had a significant effect on off-farm income.…”
Section: Overview and Concept Of Vsla In Ghanamentioning
confidence: 99%
“…Consequently, many previous studies (Aaron et al ., 2019; Karlan et al ., 2017; Lambongang et al ., 2020; Mbiro and Ndlovu, 2021; Mwansikilwa et al ., 2017; Sienso et al ., 2021) have addressed the impact of village saving groups on food and nutrition security and some other welfare indicators. Bannor et al .…”
Section: Introductionmentioning
confidence: 99%